Kwestie wyznaniowe na pograniczu polsko-niemieckim = Religius issues on the Polish-German borderland - Dudra, Stefan; Pochyły, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Religious relations on the Polish-German borderland began to take shape together with the seizure of these lands by Soviet and Polish army in 1945. Most of the abandoned Protestant churches were taken over by Catholics, and later by the Orthodox. Apart from these religions, Protestants and Greek Catholics began pastoral work in this area. Territorial changes of Poland fundamentally influenced its religious structure. The country became almost religiously homogeneous, as Roman Catholics constituted over 90% of the population.
Keywords: pogranicze polsko-niemieckie; polityka wyznaniowa; od 1945 r.